Analisis Wacana Kritis Teun A. Van Djik terhadap Teks Nasihat Ibnu Taimiyyah dalam Buku “Jangan Takut Hadapi Hidup” Karya Dr. Aidh Abdullah Al-Qarny - Firdausi Maryamah; Irfan Safrudin; Malki Ahmad Nasir (Bandung Conference Series: Islamic Broadcast Communication, 2022)
Abstract. The book "Don't Be Afraid to Face Life" is a motivational book written by a preacher from Saudi Arabia, Dr Aidh Abdullah Al-Qarny, If analyzed, in general Dr. Aidh made a text of Sheikh Ibnu Taimiyyah's advice to convey his message about the problems of life through the lens of Islam religion. In his books Dr. Aidh has written many books about human life. However, even though this advice revolves around life's problems, how to solve them according to the Islamic perspective, this book is distributed by Dr. Aidh for all humans in general. Through the discourse strategy of Teun A. Van Dijk's model to obtain three-dimensional text, social cognition and social context from the text of Sheikh Ibnu Taimiyyah's advice, the author presents a discourse analysis approach to Teun A. Van Dijk's model. The delivery of information in the text of Sheikh Ibnu Taimiyyah's advice is packaged in style. simple language. The characterizations of Sheikh Ibn Taimiyyah and other figures also seem to have characters that match the theme of the book "Don't Be Afraid to Face Life". Here, the discourse analysis of Teun A. Van Dijk captures information that the text of Sheikh Ibn Taimiyyah's advice is a representation of the state of human life that experiences various kinds of problems. Abstrak. Buku “Jangan Takut Hadapi Hidup” merupakan buku motivasi yang ditulis oleh seorang pendakwah asal Arab Saudi Dr. Aidh Abdullah Al-Qarny, Jika dianalisa, secara umum Dr. Aidh membuat teks nasihat Syekh Ibnu Taimiyyah untuk menyampaikan pesannya mengenai permasalahan kehidupan melalui kacamata agama. Dalam buku-bukunya Dr. Aidh banyak membuat buku mengenai kehidupan manusia. Namun demikian, walaupun nasihat ini berputar dalam masalah kehidupan yang cara mengatasinya menurut kacamata agama Islam, namun buku ini sendiri di bagikan Dr. Aidh untuk seluruh manusia secara umum. Melalui strategi wacana model Teun A. Van Dijk untuk mendapatkan tiga dimensi teks, kognisi sosial dan konteks sosial dari teks nasihat Syekh Ibnu Taimiyyah hemat penulis menyajikan pendekatan analisis wacana model Teun A. Van Dijk, Penyampaian informasi dalam teks nasihat Syekh Ibnu Taimiyyah dikemas dengan gaya bahasa yang sederhana. Adapun penokohan sosok Syekh Ibnu Taimiyyah dan sosok lainnya juga terlihat memiliki karakter yang sesuai dengan tema buku “Jangan Takut Hadapi Hidup”. Disini analisis wacana Teun A. Van Dijk menangkap informasi bahwa, teks nasihat Syekh Ibnu Taimiyyah merupakan salah satu representasi dari keadaan kehidupan manusia yang mengalami berbagai macam persoalan.